2020
DOI: 10.3390/foods9081017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Olive Leaf Extracts as Natural Preservative on Retailed Poultry Meat Quality

Abstract: Poultry meat is commonly marketed at refrigerated temperatures (2–5 °C). The major concern for retailers and consumers is the quality and safety of refrigerated poultry meat. During the chilling period, poultry meat undergoes too many undesirable changes due to microbial growth that leads to spoilage and economic loss. Therefore, this study was conducted to assess the effects of olive leaf extracts (OLE) used at three concentrations (0.25, 0.5, and 1%) on the sensory attributes, as well as the chemical and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 40 publications
(48 reference statements)
4
28
0
Order By: Relevance
“…Saleh et al [ 13 ] investigated the effect of olive leaf extract on the microbial quality of poultry meat. The extract reduced the total mesophilic count (TMC), TPC, total Enterobacteriaceae count, total staphylococcal count, and total mold and yeast counts, compared to the control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saleh et al [ 13 ] investigated the effect of olive leaf extract on the microbial quality of poultry meat. The extract reduced the total mesophilic count (TMC), TPC, total Enterobacteriaceae count, total staphylococcal count, and total mold and yeast counts, compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been a growing interest in the application of plant leaf extracts rich in polyphenols to meat and meat products, including olive [ 13 ], blackcurrant and sour cherry leaf extracts [ 14 ], cork oak [ 15 ], bamboo [ 16 ], eucalyptus [ 17 ], Moringa oleifera and Bidens pilosa leaf extracts [ 18 ], and curry and mint [ 19 ] leaf extracts. According to the literature, the leaves contain larger amounts of polyphenols than other parts of plants [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41] The emergence of multidrug-resistant bacteria call for the need of natural herbal alternatives to the commonly used antimicrobial agents. [42][43][44][45][46][47][48][49][50][51] The foodborne diseases resulting from the consumption of Gram-positive and Gram-negative bacteria-contaminated food have been of vital concern to public health. Good hygiene practices, adequate preservative techniques for processed foods and the use of antimicrobial substances such as antibiotics are the various control and treatment methods in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…In the study carried out by Saleh and co-workers [ 7 ], it was shown that the olive leaf extract possesses antioxidant and antimicrobial properties. This extract is able to inhibit microbial growth, and therefore increases the shelf-life of the foods to which it is added.…”
mentioning
confidence: 99%
“…Olive leaf extract is rich in polyphenolic compounds. In this work, it was determined that the extract increased the shelf-life of poultry meat, which improves the safety and quality of poultry meat and, on the other hand, reduces the economic losses caused by the decomposition of the meat [ 7 ]. The olive extract does not modify the sensory characteristics of the poultry meat.…”
mentioning
confidence: 99%